Positive or Negative Fructose Breath Test Results do not Predict Response to Fructose Restricted Diet in Children with Recurrent Abdominal Pain: Results from a Prospective Randomized Trial - Wirth, S.; Klodt, C.; Wintermeyer, P.; Berrang, J.; Hensel, K.; Langer, T.; Heusch, A. (Klinische Pädiatrie, 2014)
Objectives: To perform a prospective, blinded, randomized interventional trial in patients with recurrent abdominal pain. The primary endpoint was to determine the abdominal pain intensity after 2 weeks of fructose restricted diet. Secondary endpoints were changes of pain frequency and a secondary symptom score (SSS).Methods: 103 individuals with recurrent abdominal pain for more than 3 months were randomized. 51 patients were allocated to group A (diet) and 52 to group B (no diet). 2 weeks later the patients underwent hydrogen breath test and were assigned to the test positive or negative group to identify patients with fructose malabsorption.Results: 2 weeks after intervention the pain score decreased significantly from a median 5.5 in group A to 4 and did not change significantly in group B (5.3 to 5). In group A both patients with positive and negative breath tests had a significant lower pain score (−2 and −1.75, respectively). Frequency of abdominal pain decreased in both groups but without significant difference, SSS improved only in group A from median 6 to 3.5. Positive breath test was no predicting factor, neither was abdominal pain during the test.Conclusions: Fructose restricted diet in children and adolescents with recurrent abdominal pain may be of benefit to improve both abdominal pain symptoms and other secondary symptoms. Since a negative breath test result does not exclude a positive response to fructose restriction, the hydrogen breath test does not seem to be the appropriate diagnostic mean to predict the response to the diet.
Keywords: fructose malabsorption; recurrent abdominal pain; hydrogen breath test; fructose restricted diet; children